Neuroeconomically dissociable forms of mental accounting are altered in a mouse model of diabetes - Chinonso A. Nwakama; Romain Durand-de Cuttoli; Zainab M. Oketokoun; Samantha O. Brown; Jillian E. Haller; Adriana Méndez; Mohammad Jodeiri Farshbaf; Y. Zoe Cho; Sanjana Ahmed; Sophia Leng; Jessica L. Ables; Brian M. Sweis (Communications Biology)
Abstract Those with diabetes mellitus are at high-risk of developing psychiatric disorders, especially mood disorders, yet the link between hyperglycemia and altered motivation has not been thoroughly explored. Here, we characterized value-based decision-making behavior of a streptozocin-induced diabetic mouse model on Restaurant Row, a naturalistic neuroeconomic foraging paradigm capable of behaviorally capturing multiple decision systems known to depend on dissociable neural circuits. Mice made self-paced choices on a daily limited time-budget, accepting or rejecting reward offers based on cost (delays cued by tone pitch) and subjective value (flavors), in a closed-economy system tested across months. We found streptozocin-treated mice disproportionately undervalued less-preferred flavors and inverted their meal-consumption patterns shifted toward a more costly strategy overprioritizing high-value rewards. These foraging behaviors were driven by impairments in multiple decision-making processes, including the ability to deliberate when engaged in conflict and cache the value of the passage of time as sunk costs. Surprisingly, diabetes-induced changes in motivation depended not only on the type of choice being made, but also on the salience of reward-scarcity in the environment. These findings suggest that complex relationships between metabolic dysfunction and dissociable valuation algorithms underlying unique cognitive heuristics and sensitivity to opportunity costs can disrupt distinct computational processes leading to comorbid psychiatric vulnerabilities.